H Hubungan Dukungan Keluarga Dengan Kepatuhan Minum Obat Pada Orang Dengan Gangguan Jiwa (Odgj) di Wilayah Kerja Puskesmas Astambul - Tiara Lani; Nurul Wafa Septiana (LPPM Universitas Sari Mulia, 2022)
Background: Mental disorder is a physiological or mental condition of a person who is not functioning properly so that it interferes with daily functions, Mental disorders can function or be effective by consuming the drug, but there are several things that can hinder the success of People with Disorders (ODGJ), including non-adherence in taking medication. Destination This research is to determine the relationship between family support and adherence to taking medication in patients with mental disorders (ODGJ). Method this study used a descriptive analytic correlation study with a sample of 71 respondents. This research used the Chi-Square test. The research time was from April to July 2022. The research location was at the Astambul Community Health Center, Banjar Regency, South Kalimantan. Results In this study, it was found that there was a relationship between family support and adherence to taking medication in ODGJ patients with a p = 0.0001, which is smaller than the p > 0.05 which indicates that both variables are significantly significant. Conclusion that family support for ODGJ patients is very important in patient recovery, family support in providing positive motivation and convincing patients to adhere to taking medication, so that patients avoid relapse.